Google Site-Based Service and Trade Accounting Practice Learning Media for Grade XI Accounting Students - Rizal; Latief Sahidin; Abdullah Igo; Muh. Ilham; Murniati; Nining Gustamar (Universitas Pendidikan Ganesha, 2023)
The learning process is still using conventional learning methods. The teacher uses the module to explain the teaching material that the students have not understood by using the blackboard media. This study aims to develop Google Site-based Service and Trade Accounting Practice Learning Media for class XI accounting students. This research is development research adapted from the ADDIE development model. The Data was collected through questionnaires. The data obtained from the questionnaire were analyzed descriptively, qualitatively, and quantitatively. The study’s results consisted of five stages of making a Google Site-based Service & scoping Service &s accounting practice learning media. The eligibility level of Google Site-based Service & Trade Accounting Practice Learning Media based on assessments: Material Experts obtained a percentage of 92.61% which belongs to the Very Decent category, and Media Experts obtained a percentage of 88.89% belongs to the Very Decent category. The feasibility assessment by the trial students obtained a percentage of 88.61% which belonged to the Very Worthy category. Thus, the Google Site-based Service & Trade Accounting Practice Learning Media is very suitable for learning. Meanwhile, the results of the pre-test and post-test scores stated an increase in the average after the google site-based accounting learning media was tested from 65 to 80.